ANALISIS FAKTOR KINERJA PETUGAS KESEHATAN DI UNIT PELAYANAN TEKNIS RUMAH SAKIT KHUSUS MATA PROVINSI SUMATERA UTARA TAHUN 2022 - Rachmasari, Novita; Andreas, Rusdi; Hadi, Milvan; Anwar, Khairil (Deli Medical and Health Science Journal, 2024)
control of human assets is crucial in attaining desires. commonly, leaders assume excellent. health services will no longer run properly if the performance of the medical experts is not effective. The decline in the great of fitness offerings for eye sufferers apart from the overall performance factors of employees also can be influenced with the aid of other factors. This examine targets to decide the performance aspect analysis of health workers at UPT unique Eye sanatorium in North Sumatra Province. The populace in this have a look at had been all medical experts at UPT Eye unique health center, North Sumatra Province, particularly 148 humans with a total sample of 108 human beings. The sampling approach in this study changed into the consecutive sampling method, the information were analyzed the usage of the chi-square take a look at and logistic regression. based totally on the examine, it showed that there was a great courting between motivation, work discipline, rank magnificence, incentives, work skills, workload, tenure with the performance of medical examiners. The most dominant variable related to the overall performance of health workers is paintings area with a p-price of zero.00 where the cost of Exp (B) is 22.834 where health workers who have top work area 22 instances have appropriate performance in comparison to individuals who aren't disciplined. it's far was hoping that the clinic can pay extra interest to the performance of medical examiners such as motivation, incentives, cooperation, awards or praise for employees so one can enhance the overall performance of health workers in creating outstanding provider and assisting better paintings effects.